Characterising four Cowpea (Vigna unguiculata (L.) Walp.) Mozambican landraces deposited in a seed bank for drought tolerance - Kunert, Karl J. (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.